A review on the effectiveness of hearing conservation programme among noise-exposed employees - Ismail, Noraidah; Zakaria, Mohd Normani (Nova Science Publishers, 2022)
Noise induced hearing loss (NIHL) has been regarded as a significant occupational health problem and it is increasing throughout the industrial world. To minimize the occurrence of NIHL among noise-exposed employees, hearing conservation programme (HCP) has been introduced. In this paper, the essential aspects of NIHL are reviewed as intended. Important considerations regarding the implementation of HCP including the barriers are highlighted accordingly. Based on the existing literature, more research efforts are required to support and promote the widespread implementation of HCP among industrial players. Furthermore, studying the effectiveness of dedicated training modules in HCP involving employees using various teaching methods can be the focus of future research.